Factors Affecting Work Satisfaction in Garment Factories - Ari Pradhanawati (JURNAL ILMU SOSIAL, 2018)
Wage raise is adjusted in accordance with better quality of life. However, a lot of workers consider their current wages inadequate; in addition, the actual payment of their wages is often delayed. In consequence, work satisfaction declines. This research tests whether wages, social support, trade union activity, and worker participation influence work satisfaction. This is an explanatory research whose population is the permanent workers in the production division of a garment factory in Semarang, Indonesia. Using multiple linear regression and a Likert Scale, we examine the factors that explain work satisfaction among a sample of 100 workers in a garment factory. Our results demonstrate that wages, social support, trade union activity, and worker participation significantly influence the level of satisfactions workers have on the job.